Arthroscopic Latarjet procedure: current concepts and surgical techniques - Sang-Jin Shin; Jae Hyung Kim; Jonghyun Ahn (Clinics in Shoulder and Elbow, 2023)
The Latarjet procedure is a surgical procedure that can effectively restore glenohumeral stability, especially in patients with anterior shoulder instability and glenoid bone loss. Many studies have shown comparable clinical outcomes between patients undergoing the arthroscopic Latarjet procedure and those undergoing traditional open methods or other glenohumeral joint stabilization procedures. However, the arthroscopic Latarjet procedure is a challenging technique due to the unfamiliar portal placements, proximity of neurovascular structures, and serious postoperative complications. The arthroscopic Latarjet procedure has not yet been widely applied, and a clear understanding of the anatomical structure and the precise methods is required prior to operation performance. Satisfactory clinical outcomes can be achieved by thorough preoperative planning and proper implant fixation methods.